2010
DOI: 10.1111/j.1600-048x.2010.05075.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among timing of moult, moult duration and feather mass in long‐distance migratory passerines

Abstract: Moult is a costly but necessary process in avian life, which displays two main temporal patterns within the annual cycle of birds (summer and winter moult). Timing of moult can affect its duration and consequently the amount of material invested in feathers, which could have a considerable influence on feather structure and functionality. In this study, we used two complementary approaches to test whether moult duration and feather mass vary in relation to the timing of moult. Firstly, we conducted a comparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 25 publications
0
32
3
Order By: Relevance
“…The tendency of the overlappers to lose more body condition over time suggests that the costs of the overlap were not fully compensated, even under the benign conditions of captivity. It is possible, however, that aspects of feather quality could have been compromised in overlappers, such as feather mass or structure (Dawson et al, 2000;DesRochers et al, 2009;De la Hera et al, 2010;Strochlic and Romero, 2008;Maenniste and Horak, 2011). Further characterizations of feather structural properties in relation to molt/breeding overlap are needed to resolve this question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tendency of the overlappers to lose more body condition over time suggests that the costs of the overlap were not fully compensated, even under the benign conditions of captivity. It is possible, however, that aspects of feather quality could have been compromised in overlappers, such as feather mass or structure (Dawson et al, 2000;DesRochers et al, 2009;De la Hera et al, 2010;Strochlic and Romero, 2008;Maenniste and Horak, 2011). Further characterizations of feather structural properties in relation to molt/breeding overlap are needed to resolve this question.…”
Section: Discussionmentioning
confidence: 99%
“…Reproduction is estimated to increase daily basal metabolic rate by approximately 25-50% [egg production (King, 1973;Ricklefs, 1974;Monaghan and Nager, 1997); incubation (De Heij et al, 2008)] and molt byquality whereas for molt it would maximize feather quality and minimize deficits in flight performance (Jenni and Winkler, 1994;De la Hera et al, 2010). Indeed, in species where molt co-occurs with the end of the reproductive period, feather structure is compromised (Hemborg, 1999;Dawson et al, 2000), adult movements are restricted and survival decreases (Stearns, 1992;Hemborg and Lundberg, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…obs.). Recent research also shows that ptilochronology-based measurements of growth rate on tail feathers produced during a complete molt process are able to predict the production of feathers of higher quality than shorter molts (Dawson et al 2000, Serra 2001, Griggio et al 2009, de la Hera et al 2010b, Serra et al 2010, so selection will tend to maximize the investment of time and energy in feather production. However, the amount of time that can be allocated to molt is expected to be constrained by the temporal requirements of other important activities of the annual cycle with which molt normally does not overlap, such as breeding and migration (de la Hera et al 2009a, Rohwer et al 2011.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, some intraspecific studies have shown that a shortening of summer molt duration might be associated with a reduction in the mass and quality of feathers (Dawson et al 2000, de la Hera et al 2009b). Although there is no empirical evidence to support the extrapolation of previous patterns to the interspecific level, it has been suggested that the tradeoff between molt speed and feather mass might explain why some long-distance migratory species, which are extremely time-constrained after breeding but can occupy areas with suitable environmental conditions for molting during periods other than summer (Moreau 1972, Barta et al 2008, have adopted drastic changes in the timing of their annual complete molt (Svensson and Hedenström 1999, Hall and Tullberg 2004, de la Hera et al 2010b.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation